Persistency of Lactation, Lactation Yield, and Lactation Length in Thari Cattle at Thari Cattle Farm, Umerkot, Sindh - Kaleri, Azhar Hussain; Kaleri, Hubdar Ali; Janyaro, Habibullah; Memon, Muhammad Anees; Memon, Muhammad Awais; Rehman, Naqeeb Ur; Shahwar, Dure; Khosa, Mudasar Ahmed; Kaleri, Rameez Raja (BioScientific Review, 2025)
Background. The current study was carried out to determine the persistency of lactation in Thari cattle, in view of the impact of heritability and seasons. Method. The data on lactation length and lactation yield of Thari cattle (based on their 6 lactations) were collected for the period 2007-2017. To observe the effect of seasons on lactation persistency, the seasons were categorized as summer (April to September) and winter (October to March) for calved cows. The cows were grouped into four categories (A, B, C, and D) based on their sires to analyze the genetic effect on lactation persistency. The data were collected and analyzed using SAS software. Results. The results for the persistency of lactation revealed that it was higher in 3rd lactation (51.43± 3.85 and 57.00±3.33%) and lower in 1st lactation (39.73± 7.26 and 43.67±5.78%) of summer and winter calvers, respectively. Similarly, sire-wise persistency of milk yield and lactation length was higher in Sire D daughters (1114.33±133.11, 216.4±3.54, and 73.09±7.60) and lower in Sire A daughters (1050.87±66.24, 193.8±7.56, and 58.62±8.10), respectively. Age-wise, it was higher in Sire D daughters 81-25 (61.81 ± 6.31) and lower in Sire A daughters 73-21 (37.39 ± 7.23), respectively. The heritability estimates for milk yield, lactation length, and persistency of lactation were observed as 0.22, 0.21, and 0.11, respectively. Conclusion. The study found that the season of calving and lactation number significantly affect lactation yield, length, and persistency. On the other hand, there was no significant difference observed with reference to paternity. Lactation yield and length were higher in the 3rd lactation for both summer and winter calvers, while lower in the 1st lactation for both seasons. The heritability of milk yield, lactation length, and persistency was low, suggesting that improvements can be made through better management and by avoiding inbreeding.